Kepemimpinan Transformasional Kepala Madrasah dalam Meningkatkan Mutu Pembelajaran di MI PAS Baitul Qur’an Sudimoro, Mlarak, Ponorogo - Fardati, Fadhliya; Sulton, Sulton (Universitas Muhammadiyah Ponorogo, 2026)
This research aims to analyze the implementation of the headmaster's transformational leadership and its role in improving the quality of learning at Madrasah Ibtidaiyah Pesantren Anak Sholeh (MI PAS) Baitul Qur’an Sudimoro, Ponorogo. The main focus of the study lies in how the dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration are integrated into the boarding school-based madrasah ecosystem. This research uses a qualitative approach with a descriptive case study type. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The research results show that the headmaster's transformational leadership succeeded in transforming traditional obedience into professional commitment, which had an impact on the escalation of teacher professionalism and innovation in learning strategies such as Project Based Learning (PjBL). The leader acts as a catalyst in synergizing Qur'anic values with 21st-century competencies and civic character. The success of this quality transformation is supported by the solidity of the foundation's vision and a supportive organizational culture, even though it still faces challenges regarding limited physical facilities. The research conclusion confirms that adaptive and exemplary-based transformational leadership is the main key to increasing the madrasah's competitiveness in the era of disruption.